Assessment Model for Programmatic Diversity, Equity, Inclusion, and Belonging Initiatives - Esteves Miranda, Vianka; Elizabeth Abington Prejean (International Journal of Business and Social Science Research, 2023)
The study of diversity, equity, inclusion, and belonging, (DEIB) processes are an ever-evolving phenomenon that will continue to influence and change the world. These processes are becoming increasingly prevalent and are present in business and educational environments driven by societal demands, environmental awareness, and funding requirements. The next generation of business leaders has serious concerns about the environment they will soon inherit. Each generation has events that define them (Civil Rights Movements, Watergate, the Recession, the Clinton Administration and Y2K, the Great Recession, Global Warming and Climate Change). Today's students want to make a positive difference on Earth, unlike any generation in the past half-century. Furthermore, higher education faculty and administrators must meet the charge of effectively preparing post-secondary graduates to function in these initiatives.